Data and code supporting the paper "Competing adsorption of H and CO on Pd-alloy surfaces: Mechanistic insight into the mitigating effect of Cu on CO poisoning" - Ekborg-Tanner, Pernilla; Erhart, Paul (Chalmers University of Technology, 2026)
This record contains machine-learned interatomic potential (MLIP) and cluster expansion (CE) models for the AuCuPd:CO,H system along with reference data from density functional theory (DFT) calculations. Technical details are provided in

Pernilla Ekborg-Tanner and Paul ErhartCompeting adsorption of H and CO on Pd-alloy surfaces: Mechanistic insight into the mitigating effect of Cu on CO poisoningdoi: https://doi.org/10.48550/arXiv.2603.00776

MLIP models

Models based on the neuroevolution potential (NEP) architecture are provided in the nep-*.txt files. The "full" model has been trained against all available data whereas the "split" models have been trained against a random selection of 90% structures from the available structures.

Models based on the MACE architecture are provided in the MACE-*.model files.

CE models

Models are provided for (111), (110), and (100) surfaces in the *.ce files along with reference structures in the *.xyz files

Reference data

Reference data from DFT calculations is provided in the reference-structures.db file, which is a sqlite database generated using the ase package.
Keywords: Cluster expansions; Machine-learned interatomic potential; Neuroevolution potential; Monte Carlo simulations; Surfaces; Surface segregation; Physical Sciences; Fysik